Bioprosthetic tricuspid valve endocarditis caused by Acinetobacter baumannii complex, a case report and brief review of the literature. Issue 1 (December 2015) - Chen, Qiang; Cao, Hua; Lu, Heng; Qiu, Zhi-huang; He, Jia-jun
Abstract Background Species of the genusAcinetobacter are Gram-negative and highly drug-resistant bacilli that normally reside on the skin, oropharynx, and perineum. Several previous studies have reported prosthetic valve endocarditis due toA. baumannii infection. Case presentation Here we present a case of late endocarditis of a bioprosthetic tricuspid valve due toA. baumannii complex in a patient who had surgical replacement with a bioprosthetic tricuspid valve six years previously. Conclusions We completed tricuspid valve replacement using a 29 mm St. June mechanical prosthetic valve for the patient. Postoperatively, she received intravenous cefoperazone sodium and sulbactam sodium for 2 months and had good recovery.